1998
DOI: 10.1042/cs0950557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium nitroprusside and L-arginine methyl ester on rat hearts stored at 4 °C for 24 h

Abstract: 1. This study examined the effects of altering nitric oxide levels with sodium nitroprusside or L-arginine in rat hearts stored hypothermically.2. Hearts were microperfused at 4 degrees C for 24 h with a modified Krebs-Henseleit buffer (KHB) that contained either sodium nitroprusside, L-arginine, L-arginine methyl ester or dexamethasone.3. After hypothermic storage, hearts were rewarmed to 37 degrees C with KHB alone or KHB containing sodium nitroprusside or L-arginine. Cardiac function was then assessed in ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Other studies showed that L-NAME, N G -monomethyl-L-arginine and oxyhemoglobin, all NO ⅐ scavengers, provide protection against I/R injury (50). However, Fagbemi and Northover (20) showed that the presence of NO ⅐ donors and not inhibitors in the cold buffer improved coronary flow during subsequent warm reperfusion. In any case, these studies demonstrate a significant role of NO ⅐ in the pathogenesis of cold-induced I/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed that L-NAME, N G -monomethyl-L-arginine and oxyhemoglobin, all NO ⅐ scavengers, provide protection against I/R injury (50). However, Fagbemi and Northover (20) showed that the presence of NO ⅐ donors and not inhibitors in the cold buffer improved coronary flow during subsequent warm reperfusion. In any case, these studies demonstrate a significant role of NO ⅐ in the pathogenesis of cold-induced I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Portions of this work were presented in abstract form at the 48th Annual Meeting of the Biophysical Society, Baltimore, MD, February 14 -18, 2004, and at the Experimental Biology Conference, Washington, DC, April [17][18][19][20][21] 2004.…”
Section: Acknowledgmentsmentioning
confidence: 99%